Comparison of Alternative Solutions to Workload and Welfare of Civil Servants Linear Employee Performance and Burnout - Luran, Muhammad Fadli; Adnan, A.; Amirullah, A. (Manunggal Halim Jaya, 2025)
Law Number 5 of 2014 states that ASN is a profession for civil servants and government employees who work in government agencies within employment agreements. ASN employees are required to follow several rules and be loyal and obedient to Pancasila, 1945 Constitution of the Republic of Indonesia. Based on the initial research survey at Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province as well as the introductory description, the fundamental problems identified as material for analysis and discussion of this research related to excessive workload through burnout or fatigue at work has a significant effect on the performance of Civil servants in two government agencies, Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. Research targeted and focused on identifying the influence of workload on the performance of civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. Identify influences of burnout on the performance of civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. Identify the impact of workload and burnout simultaneously on the performance of civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. The research findings indicate no significant influence in the negative direction of workload on employee performance in civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. There is no significant influence in the negative direction of workload on burnout for civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. There is a significant favorable influence on the welfare of civil servants' performance at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. There is no significant influence in the positive direction of the welfare of civil servants on burnout for civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province. There is no significant favorable influence on employee performance burnout for civil servants at the Population and Civil Registry Service and Manpower and Transmigration Service of Riau Islands Province.